Aeromagnetic-Imaged Basement Fault Structure of the Eastern Tarim Basin and Its Tectonic Implication - Kuang, Xingtao; Zhu, Xiaoying; Ning, Fangxin; Li, Wei; Zheng, Qifang; Li, Bing; Zhou, Daoqing (Frontiers in Earth Science, 2022)
The property of the magnetic basement and the faults in the basement is significant for the structural evolution, the Phanerozoic deposition and oil resource exploration of Tarim Basin. Based on the newly-acquired aeromagnetic and industry seismic data, we mapped the distribution of basement faults by applying the magnetic gradient-processing methods such as the horizontal gradient derivative, the first vertical derivative, the tilt derivative, and the upward continuation type method. The dips of basement faults were confirmed and the susceptibilities of basement blocks were obtained by forward modeling of five profiles using the constraint of sedimentary strata depth and Moho topography. On the basis of comprehensive analysis of the magnetic anomalies, the distribution and inclination of basement faults, susceptibilities differentiation obtained by forward modeling and field measurement, the property of the basement faults and their implication were discussed and interpreted. Our results show that the origin of the Central Highly Magnetic Anomaly Belt was the Archean highly-magnetic metamorphic rocks. The weakly-magnetic Southeastern Domain and highly-magnetic Central Tadong Domain assembled along the Tadong South Fault during the Paleoproterozoic. The Paleozoic Cherchen Fault is just an interior fault in the weakly-magnetic Southeastern Domain although it presents a large vertical fault displacement. Considering the prominent variation of strikes of Tadong North Fault system, and the moderately magnetic anomalies in the Northeastern Mangal Domain corresponding to the center of Neoproterozoic deposition, it is likely that the basement of the Northeastern Mangal Domain modified by the Neoproterozoic rifting could be originally the same as the Central Highly Magnetic Anomaly Belt.